1999
DOI: 10.1136/jcp.52.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of p53 gene and SV40 sequences in asbestos associated and non-asbestos-associated mesotheliomas.

Abstract: Aim-To examine mesotheliomas for a possible relation between p53 immunostaining, p53 gene mutation, simian virus 40 (SV40), and asbestos exposure. Methods-ParaYn sections from 11 mesotheliomas were used for p53 immunostaining and also to extract DNA. This was analysed for the presence of mutations in exons 5 to 8 of the p53 gene using a "cold" single strand conformational polymorphism method, together with sequencing. The DNA from the paraYn sections was also used to search for SV40 sequences. A 105 base pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…The direct involvement of SV40 Tag expression in the growth of malignant mesothelioma cells has been described (8), and SV40 is associated with a shorter survival of MM patients (9). A synergistic action between SV40 and asbestos fibers has been suggested (10), and HMC have been shown to be highly sensitive to SV40-mediated transformation (11).…”
Section: Alignant Mesothelioma (Mm) Is An Aggressive and Invasivementioning
confidence: 99%
“…The direct involvement of SV40 Tag expression in the growth of malignant mesothelioma cells has been described (8), and SV40 is associated with a shorter survival of MM patients (9). A synergistic action between SV40 and asbestos fibers has been suggested (10), and HMC have been shown to be highly sensitive to SV40-mediated transformation (11).…”
Section: Alignant Mesothelioma (Mm) Is An Aggressive and Invasivementioning
confidence: 99%
“…None of the non-asbestos associated mesotheliomas were positive for SV40. Mayall suggested the possibility of a synergistic relationship between SV40 and asbestos in the development of malignant mesothelioma (Mayall et al, 1999).…”
Section: Sv40 and Human Mesotheliomamentioning
confidence: 99%
“…Only one mutation in the p53 suppressor gene has been found in fifteen malignant mesothelioma patients, a GGA TGA transversion in codon 266 (Exon 8) 6) . Also, one silent mutation has been observed in the p53 suppressor gene of eleven primary malignant mesothelioma patients 7) . In other studies, no alteration in the Ha-ras oncogene was found in eleven primary tumors of malignant mesothelioma including those from cases with asbestos exposure 8) , and no alteration in the p53 suppressor gene was demonstrated in thirteen primary tumors of malignant mesothelioma, of which only two cases had a history of asbestos exposure 9) .…”
Section: Introductionmentioning
confidence: 99%